First discovery of a new species of Newmanella Ross, 1969 (Balanomorpha: Tetraclitidae) in the western Pacific, with a note on the new status of Neonrosella Jones, 2010 - Chan, Benny K.k.; Cheang, Chi Chiu (Zootaxa, 2016)
The present study describes a new species of Newmanella Ross, 1969 (Thoracica: Tetraclitidae: Newmanellinae) from Taiwan. Species in this genus are believed to be distributed in tropical western Atlantic waters and the present study is the first report of a new species of Newmanella in the western Pacific. Newmanella spinosus sp. nov. is morphologically close to N. radiata Bruguiére, 1789 but it is distinguished from N. radiata by the morphology of the scutum, tergum, cirrus II, mandible and maxillule. Sequence divergence of 12S rDNA between N. radiata and N. spinosus sp. nov. reached 7.6%, suggesting these are two different species. Newmanella spinosus sp. nov. is distributed in the Philippines, Taiwan and Okinawa but is absent from Hong Kong, Hainan and China. The distribution is probably affected by the Kuroshio Current. The subfamily Newmanellinae Ross and Perreault, 1999 contains two genera, Newmanella and Yamaguchiella Ross & Perreault, 1999. Neonrosella Jones, 2010 is a subgenus of Yamaguchiella. A recent molecular analysis (Tsang et al. 2015) determined that Yamaguchiella and Neonrosella are located in two distinct and distantly-related clades within the tetraclitid clade, suggesting that the subgenus Neonrosella is not closely related to Yamaguchiella and should be elevated to generic status.